PENINGKATAN KESADARAN REMAJA MELALUI EDUKASI BAHAYA MEROKOK UNTUK MENCEGAH TUBERKULOSIS PARU - Riski Tri Wijayanti; Purista Tiara Dewi; Karina Dwi Hapsari; Nining Lestari; Adam Fauzi (PT. Hasba Edukasi Mandiri, 2025)
Tuberculosis (TB) remains a major public health problem in Indonesia, with smoking recognized as one of its key risk factors. This community service activity aimed to increase adolescents’ awareness of the dangers of smoking and its relationship with pulmonary tuberculosis through an educational session at SMA Muhammadiyah 1 Surakarta. The method included interactive education, discussions, and pretest–posttest assessments to evaluate participants’ knowledge improvement. A total of 28 eleventh-grade students participated. The results showed that the average pretest score was 80.36, which increased to 92,8 in the posttest, showing an improvement of 12.85 points. This activity effectively enhanced students’ understanding of the dangers of smoking and the importance of tuberculosis prevention. Similar programs are expected to be continued in schools to promote healthy lifestyles.